The 19th Christmas - Patterson, James , 1947-; Paetro, Maxine (New York : Little, Brown and Company, 2019)
As the holidays approach, Detective Lindsay Boxer and her friends are celebrating the fact that crime is down. Soon, a criminal known only as "Loman" shows up in the headlines.
Keywords: Boxer, Lindsay -- (Fictitious character) -- Fiction; Murder -- Investigation -- Fiction; Terrorism -- Fiction; Suspense fiction; Christmas fiction; Thrillers (Fiction); Detective and mystery fiction; San Francisco (Calif.) -- Fiction